Mountain ranges and geographical isolation increase bird taxonomic but not phylogenetic beta diversity in the megadiverse Paramo ecosystems - Calpa-Anaguano, Edna Viviana (2019)
Understanding present-day biodiversity of Neotropical mountain regions requires knowledge of its historical and ecological conditions. We evaluated how Andean uplift, Quaternary climatic oscillations, current climate, and geographical isolation are associated to the spatial distribution of taxonomic and bird phylogenetic beta (β) diversity in the Paramo ecosystems in the Andes mountains in southwestern Colombia. Using point occurrence data for 175 bird species recorded in 11 Paramos, we calculated taxonomic β-diversity (TβD) using Simpson index, and phylogenetic β-diversity (PβD) using PhyloSorturn. We made a lineage through time (LLT) plot to evaluate the association between bird species richness and the final phase of Andean uplift and Quaternary climatic oscillations. We also used a model selection procedure with Generalized Linear Models to generate competing models that explain the variation in TβD and PβD distributions. Two thirds of the bird species in the Paramo ecosystems are recent and emerged after the late Miocene/early Pliocene. The average taxonomic β-diversity was four times higher than the average phylogenetic β-diversity indicating that Paramo assemblages are harboring different bird species, but they are closely related (e.g., same genera). Furthermore, places with high altitudinal range difference and geographically isolated had higher taxonomic and phylogenetic β-diversity than Paramos with similar altitudinal ranges and close to each other. The final phase of the Andes uplift impacted avian speciation in the Paramo ecosystem, reflecting in high values of taxonomic β-diversity, but not phylogenetic β-diversity. The Quaternary climatic oscillations might have facilitated bird dispersal between close localities contributing to the association of TβD and PβD to geographical isolation (e.g. distance decay of similarity). Our results demonstrated that the integration of different facets of β-diversity into a community ecology framework provides new insights to understand historical and ecological factors responsible for generating patterns of species distribution.